2014
DOI: 10.1007/s10158-014-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

The method of isolation of the crayfish abdominal stretch receptor maintaining a connection of the sensory neuron to the ventral nerve cord ganglion

Abstract: The crayfish stretch receptor consisting of the single mechanoreceptor neurons enveloped by satellite glial cells is the simplest functioning neuroglial preparation. However, during isolation, its axons are usually transected that eliminates afferent regulation and induces complex axotomy-related signaling responses in neurons and satellite glia. We developed new microsurgical method of crayfish stretch receptor isolation, which preserves connections of sensory neurons to the ventral nerve cord ganglion. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Eight hours of incubation of a sample in saline are sufficient for the appearance of morphological signs (fragmented nuclei) of spontaneous or induced glial apoptosis. The apoptosis did not increase in the following hour of incubation in intact samples (so it is a spontaneous apoptosis), but continued to grow in axotomized cells [113], thus suggesting that AT is a long-lasting damaging factor, although the lumen was instantly sealed mechanically after the transection [19]. Our further analysis showed that AT makes remote glia susceptible to apoptosis promoted by increased extracellular Ca 2+ and impaired the functions of ryanodine receptors and ER Ca 2+ ATPase (SERCA).…”
Section: Cell Death Scenarios In Neurons and Glia After Axotomymentioning
confidence: 96%
See 1 more Smart Citation
“…Eight hours of incubation of a sample in saline are sufficient for the appearance of morphological signs (fragmented nuclei) of spontaneous or induced glial apoptosis. The apoptosis did not increase in the following hour of incubation in intact samples (so it is a spontaneous apoptosis), but continued to grow in axotomized cells [113], thus suggesting that AT is a long-lasting damaging factor, although the lumen was instantly sealed mechanically after the transection [19]. Our further analysis showed that AT makes remote glia susceptible to apoptosis promoted by increased extracellular Ca 2+ and impaired the functions of ryanodine receptors and ER Ca 2+ ATPase (SERCA).…”
Section: Cell Death Scenarios In Neurons and Glia After Axotomymentioning
confidence: 96%
“…In crayfish stretch receptors, AT not only decreased firing duration (the functional "lifetime") of mechanoreceptor neurons [19], but also promoted necrosis and apoptosis of remote glial cells (RGC) [30,113]. Eight hours of incubation of a sample in saline are sufficient for the appearance of morphological signs (fragmented nuclei) of spontaneous or induced glial apoptosis.…”
Section: Cell Death Scenarios In Neurons and Glia After Axotomymentioning
confidence: 99%
“…The structure of the MRN is shown in Figure 1a. Satellite glial cells (SGC) and their interaction with MRN were studied in detail at the optical and ultrastructural levels [12][13][14][15][16]. MRN generates impulses directed to the VNC ganglion with a frequency proportional to the lengthening of the receptor muscle, which is strengthened.…”
Section: Crayfish Stretch Receptor (Csr)mentioning
confidence: 99%
“…MRN axotomy was performed by cutting the axon at a distance of 5-8 mm from the cell body. We have developed a technique for isolating control MRNs, the axon of which is not cut and retains a connection with the VNC ganglion [14]. The technique of MRN isolation and axotomy is described in more detail in our previous works [14,54].…”
Section: Crayfish Stretch Receptor (Csr)mentioning
confidence: 99%
See 1 more Smart Citation